Efficacy and safety of apatinib or anlotinib combined with PD-1 inhibitors-based therapy as subsequent-line treatment for recurrent or metastatic nasopharyngeal carcinoma: a real-world retrospective study - Gao, Jingjing; Xu, Jingshu; He, Yiyue; Zong, Dan; Jin, Tong; He, Xia (Frontiers in Oncology, 2025)
BackgroundRecurrent or metastatic nasopharyngeal carcinoma (R/M NPC) that progresses following first-line treatment often ends up with a poor prognosis, and no standard regimens have been established universally. Preclinical studies have suggested that combining vascular endothelial growth factor (VEGF) inhibitors with immune checkpoint inhibitors (ICIs) may exert synergistic antitumor effects. This real-world study aimed to evaluate the efficacy and safety of programmed death-1 (PD-1) inhibitors plus either apatinib or anlotinib, with or without chemotherapy, as a subsequent-line treatment in patients with R/M NPC.MethodsBetween January 1, 2018, and December 12, 2024, a total of 154 patients with R/M NPC were included and treated with various modes of combinations (ITC, IT, IC, I). Among them, 65 received apatinib or anlotinib plus PD-1 inhibitors (ITC+ IT, combination group), and 89 did not receive the addition of apatinib or anlotinib (IC+I, non-combination group). The primary endpoint was progression-free survival (PFS); the secondary endpoints included overall survival (OS), objective response rate (ORR), disease control rate (DCR), and treatment-related adverse events (TRAEs).ResultsAs of February 28, 2025, the median follow-up duration was 28.7 months (range 1.3-62.7 months). Compared with the non-combination group, the combination group showed significantly prolonged PFS (20.8 vs. 8.2 months; HR: 0.46, 95% CI: 0.32–0.69; P < 0.001) and OS (34.7 vs. 23.6 months; HR: 0.58, 95% CI: 0.35–0.96; P = 0.042). The combination group also demonstrated higher ORR (47.0% vs. 31.5%; P = 0.041) and DCR (90.8% vs. 82.0%; P = 0.126). The overall incidence of TRAEs was slightly higher in the combination group (96.9% vs. 93.3%; P = 0.599). No treatment-related deaths were reported in either group.ConclusionIn patients with R/M NPC that progressed after first-line therapy, the combination of anti-angiogenic agents (apatinib or anlotinib) with PD-1 inhibitors based therapy demonstrated a promising antitumor efficacy and an acceptable safety profile. These findings were consistent even among patients from non-endemic regions.